Nanoparticle accumulation and penetration in 3D tumor models: the effect of size, shape, and surface charge - Cybulski, Pierre; Bravo, Maria; Chen, Jim Jui-Kai; Van Zundert, Indra; Krzyzowska, Sandra; Taemaitree, Farsai; Uji-i, Hiroshi; Hofkens, Johan; Rocha, Susana; Fortuni, Beatrice (Frontiers in Cell and Developmental Biology, 2025)
Preclinical studies have demonstrated that nanoparticles (NPs) hold significant potential for advancing cancer therapy by enhancing therapeutic efficacy while reducing side effects. Their effectiveness in solid tumors is, however, often constrained by insufficient accumulation and penetration. Understanding how the physicochemical properties of NPs – such as size, shape, and surface charge – influence their interaction with cells within the tumor is critical for optimizing NP design. In this study, we addressed the challenge of inconsistent NP behavior by systematically evaluating NP uptake in both 2D and 3D tumor models, and NP penetration in spheroids. Our results showed that larger NPs exhibited higher internalization rates in 2D models but limited penetration in 3D spheroids. Furthermore, negatively charged NPs consistently achieved superior accumulation and deeper penetration than neutral and positively charged NPs. Spherical NPs outperformed rod-shaped NPs in tumor accumulation and penetration. These findings underscore the importance of carefully tailoring NP properties to the complex tumor microenvironment for improved therapeutic outcomes in real tumors.